PENGARUH VARIASI LATIHAN PASSING TERHADAP KETERAMPILAN PASSING PEMAIN FUTSAL SMA NEGERI 13 KOTA JAMBI - Dinda S.; Ilham; Munar, Hendri; Yuliawan, Ely (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
During the match, the passing skills of the players at Negeri 13 Kota Jambi were still inaccurate, with passes not hitting the target accurately, and their passing skills lacking. The author's observations at the time revealed that many of the 17 players still made inaccurate passes. Of the 17 players, 12 had average passing skills (71%), and 5 had poor passing skills (29%). This research used an experimental method. One experimental group was intentionally given a treatment. The research design used a One Group Pretest-Postest Design. The treatment group was given a pretest before the treatment was administered, followed by a posttest at the end of the treatment. Due to the relatively small population, 24 participants were sampled using total sampling. Based on the analysis results obtained from the t-test, the comparison of the calculated t value with the percentile value in the t-distribution table, for a significance level of α = 0.05 with degrees of freedom (dk) = (n - 1) = 23, obtained t count (12.46) > t table (1.7139). After the discussion above, the analysis conducted, this study can be concluded that there is an effect of passing training variations on the passing skills of futsal players at SMA Negeri 13 Kota Jambi with t count > t table.